Depression affects autonomic system of the body? Yes, it does! - Sheena Singla; Shikha Jhamb; Kamal Dev Singh; Avnish Kumar (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Depression is a disorder of the brain, a state of low mood and aversion to activity that can affect a person's thoughts, behavior, feelings, and sense of well-being and can cause alteration in sympathetic activity of the body, thus affecting heart rate variability (HRV). AIM: The study was conducted to determine the effects of depression on HRV parameters in clinically known cases of depression. MATERIALS AND METHODS: A cross-sectional (observational) study was conducted on fifty known patients of depression, aged 18-65 years, and fifty healthy, age-matched, normal controls. HRV test was conducted, and the results were analyzed statistically using Student's "t"-test for equal variance, for various parameters. RESULTS: The study showed that the differences in mean R-R interval(s), mean HR (beats/min), very low frequency (VLF) power (milliseconds squared [ms2]), and low frequency/high frequency (LF/HF) power (%) (LF/HF ratio) among controls and cases were statistically highly significant, while the differences in LF power (ms2) in controls and cases were statistically significant. However, the differences in basic anthropometric parameters, STD (standard deviation of the normal to normal)(s), root mean square successive difference (ms), NN50 (count), pNN50 (%), VLF peak (Hz), LF peak (Hz), HF peak (Hz), HF power (ms2), VLF power (%), LF power (%), HF power (%), LF power (nu), and HF power (nu) were found to be statistically insignificant. CONCLUSION: Depression leads to changes in autonomic control of the body and changes the autonomic balance in favor of an increased sympathetic tone, which can be detected with fair accuracy with HRV analysis.